Exercises 2.3
⇒
s
Z
0
d
[
µ
(
x
)
y
]=
s
Z
0
µ
(
x
)
xdx
⇒
µ
(
x
)
y
(
x
)
±
±
±
x
=
s
x
=0
=
s
Z
0
µ
(
x
)
xdx
⇒
µ
(
s
)
y
(
s
)
−
µ
(0)
y
(0) =
s
Z
0
µ
(
x
)
xdx.
From the initial condition,
y
(0) = 2. Also, note that
µ
(0) = exp
0
Z
0
p
1+sin
2
tdt
=
e
0
=1
.
This yields
µ
(0)
y
(0) = 2 and so
µ
(
s
)
y
(
s
)=
s
Z
0
µ
(
x
)
xdx
+2
.
Dividing by
µ
(
s
) and interchanging
x
and
s
give the required.
(b)
The values of
µ
(
x
),
x
=0
.
1, 0
.
2,
...
,1
.
0, approximated by using Simpson’s rule, are
given in Table 2C.
Table 2–C
: Approximations of
ν
(
x
)=
R
x
0
√
1+sin
2
tdt
and
µ
(
x
)=
e
ν
(
x
)
using Simpson’s
rule.
x
ν
(
x
)
ν
(
x
)
ν
x
)
µ
(
x
)
µ
(
x
)
µ
(
x
)
x
ν
(
x
)
ν
(
x
)
(
x
)
µ
(
x
)
µ
(
x
)
µ
(
x
)
0.0
0.0
1.0000
0.6
This is the end of the preview. Sign up
to
access the rest of the document.
This note was uploaded on 03/29/2010 for the course MATH 54257 taught by Professor Hald,oh during the Spring '10 term at Berkeley.
 Spring '10
 Hald,OH
 Math, Differential Equations, Linear Algebra, Algebra, Equations

Click to edit the document details